2011
DOI: 10.1038/ncb2260
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement for the dual functions of β-catenin in embryonic stem cell self-renewal and germ layer formation

Abstract: Canonical Wnt-signalling has been implicated in mouse and human embryonic stem cell (ESC) maintenance, however its requirement is controversial. β-catenin is the key component in this highly conserved Wnt pathway, acting as a transcriptional transactivator. Yet, β-catenin has additional roles at the plasma membrane regulating cell-cell adhesion, complicating the analyses of cells/tissues lacking β-catenin. We report here the generation of a β-catenin deficient mouse ESC (mESC) line and show that self-renewal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

45
254
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 228 publications
(304 citation statements)
references
References 67 publications
(93 reference statements)
45
254
3
2
Order By: Relevance
“…Another approach independently taken by two groups (Austin Smith's group and Christine Hartmann's group) found that after conditionally ablating b-catenin from established mESC lines, cells formed abnormally scattered colonies consisting of poorly attached cells (Lyashenko et al 2011;Wray et al 2011), which was similar to the colony morphology of outgrowths from b-catenin-null blastocysts (Haegel et al 1995). Interesting, the abnormal colony morphology returned to normal after several passages despite the continued absence of b-catenin, most likely because plakoglobin, a homolog of b-catenin that also binds to E-cadherin, replaced b-catenin at adherence junctions (Haegel et al 1995;Huelsken et al 2000;Lyashenko et al 2011). Ablating b-catenin failed to block pluripotent cell proliferation in either 2i þ LIF or LIF þ ERK inhibitor conditions (Lyashenko et al 2011;Wray et al 2011).…”
Section: Mechanisms Of Wnt Pathway Effects On Pluripotent Cells Gsk3 mentioning
confidence: 99%
See 4 more Smart Citations
“…Another approach independently taken by two groups (Austin Smith's group and Christine Hartmann's group) found that after conditionally ablating b-catenin from established mESC lines, cells formed abnormally scattered colonies consisting of poorly attached cells (Lyashenko et al 2011;Wray et al 2011), which was similar to the colony morphology of outgrowths from b-catenin-null blastocysts (Haegel et al 1995). Interesting, the abnormal colony morphology returned to normal after several passages despite the continued absence of b-catenin, most likely because plakoglobin, a homolog of b-catenin that also binds to E-cadherin, replaced b-catenin at adherence junctions (Haegel et al 1995;Huelsken et al 2000;Lyashenko et al 2011). Ablating b-catenin failed to block pluripotent cell proliferation in either 2i þ LIF or LIF þ ERK inhibitor conditions (Lyashenko et al 2011;Wray et al 2011).…”
Section: Mechanisms Of Wnt Pathway Effects On Pluripotent Cells Gsk3 mentioning
confidence: 99%
“…Although GSK3 activity is necessary for regulating b-catenin levels, it is also important for cellular effects not normally associated with Wnt signaling, such as glycogen metabolism and translation control (Doble and Woodgett 2003). Moreover, the suggestion that b-catenin was not genetically necessary for mESCs to proliferate in LIF þ serum conditions (Lyashenko et al 2011;Wray et al 2011) presented the possibility that b-catenin-independent effects of GSK3 inhibition and Wnt stimulation may affect pluripotent cell self-renewal. Therefore, it was important to determine if Wnt stimulation/Gsk3 inhibition affects function through b-catenin.…”
Section: Mechanisms Of Wnt Pathway Effects On Pluripotent Cells Gsk3 mentioning
confidence: 99%
See 3 more Smart Citations